7x-2y=0

Subtract 7x from both sides of the equation.

-2y=-7x

Divide each term by -2 and simplify.

Divide each term in -2y=-7x by -2.

-2y-2=-7x-2

Cancel the common factor of -2.

Cancel the common factor.

-2y-2=-7x-2

Divide y by 1.

y=-7x-2

y=-7x-2

Dividing two negative values results in a positive value.

y=7×2

y=7×2

y=7×2

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=7(0)2

Simplify 7(0)2.

Cancel the common factor of 0 and 2.

Factor 2 out of 7(0).

y=2(7⋅(0))2

Cancel the common factors.

Factor 2 out of 2.

y=2(7⋅(0))2(1)

Cancel the common factor.

y=2(7⋅(0))2⋅1

Rewrite the expression.

y=7⋅(0)1

Divide 7⋅(0) by 1.

y=7⋅(0)

y=7⋅(0)

y=7⋅(0)

Multiply 7 by 0.

y=0

y=0

Use the x and y values to form the ordered pair.

(0,0)

(0,0)

Remove parentheses.

y=7(1)2

Multiply 7 by 1.

y=72

Use the x and y values to form the ordered pair.

(1,72)

(1,72)

Remove parentheses.

y=7(2)2

Cancel the common factor of 2.

Cancel the common factor.

y=7⋅22

Divide 7 by 1.

y=7

y=7

Use the x and y values to form the ordered pair.

(2,7)

(2,7)

These are three possible solutions to the equation.

(0,0),(1,72),(2,7)

Find Three Ordered Pair Solutions 7x-2y=0